Synthesis of Ni3Al/ZrO2 nanocomposite and study on its high temperature oxidation in mixed gas environment - Ismail, Roslina; Yaacob, Iskandar Idris (Trans Tech Publications, 2010)
Intermetallic nanocomposites of nickel aluminide (Ni3Al) alloy and nanosized zirconia (ZrO2) were fabricated using combined powder metallurgy technique and reaction synthesis. Nanosized zirconia as dispersed phase at 2 and 5 weight percent were pre-mixed with nickel, aluminum powders and other alloying elements in a planetary ball mill for 18 hours at 175 rpm to achieve mechanical alloying effect. The mixture was then compacted using a hydraulic press at 400MPa for 15 minutes. Sintering was done under inert condition (flowing Argon gas) in a tube furnace at 850°C with 3 hours holding time. The saturation magnetization (Ms) values of nickel aluminide nanocomposites containing 2wt% ZrO2 (ICZ2) and 5wt% ZrO2 (ICZ5) were 7.94 and 3.65 emu/g respectively. Reduced elastic modulus (Er) for ICZ5 was lower than ICZ2. Isothermal oxidation/sulfidation test in 1%SO2/air gas mixture at 800 and 1000°C were performed using a thermogravimetric analyzer (TGA) for up to 24 hours duration. The isothermal kinetic results for ICZ2 and ICZ5 are parabolic indicating rate limiting step. Reaction rates increased with increasing temperature. At this low concentration of sulfur, the test specimen only exhibited adsorption of sulfur in the vicinity of the surface region and no sulfide phase was observed. © (2010) Trans Tech Publications.